Flexible and Alternately Layered High‐Loading Film Electrode based on 3D Carbon Nanocoils and PEDOT:PSS for High‐Energy‐Density Supercapacitor. (24th February 2022) - Huang, Hui; Zhao, Yongpeng; Cong, Tianze; Li, Chengwei; Wen, Ningxuan; Zuo, Xueqing; Guo, Yuan; Zhang, Hao; Fan, Zeng; Pan, Lujun
Abstract: The development of flexible carbon‐based film electrodes with high loading and sufficient electron/ion transport channels is of great significance but still challenging. Herein, a flexible high‐loading (over 15 mg cm –2 ) film with 3D hierarchical pores is prepared by an alternate deposition of carbon nanocoils (CNCs) and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The unique alternate architecture of CNC/PEDOT:PSS bilayers possesses porous structure constructed by interconnected CNCs, which serves as transfer channels and storage chambers of ions. Meanwhile, the PEDOT:PSS layers anchoring CNCs function as not only the cement to ensure the stability of the film structure but also the current collectors to improve electron transfer kinetics between interlayers. The film electrode shows excellent flexibility and electrochemical properties. It delivers a high areal capacitance of 1402.5 mF cm –2 at 0.25 mA cm –2 and a superior stability even at an extremely high current density of 50 mA cm –2 after 10 000 cycles. The corresponding solid‐state supercapacitor has great energy storage ability and steady capacitance response under various deformation. The device achieves a superb energy density of 211 μW h cm –2 with a wide potential window of 2 V. This strategy paves a road for the controllable fabrication of high‐performance flexible electrodes and supercapacitors. Abstract : A flexible and high‐mass‐loading (over 15 mg cm −2 ) film with 3D connected hierarchical pores is constructed by an alternate layer‐by‐layer deposition of carbon nanocoils (CNCs) and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The alternatively layered film shows an ideal electrode structure in which electrons transfer along the 3D conductive network of PEDOT:PSS and CNCs, while ions are transported and stored in the connected pores.